Mechanism and functional impact of CD40 ligand-induced von Willebrand factor release from endothelial cells - Möller, Kerstin; Adolph, Oliver; Grünow, Jennifer; Elrod, Julia; Popa, Miruna; Ghosh, Subhajit; Schwarz, Manuel; Schwale, Chrysovalandis; Grässle, Sandra; Huck, Volker; Bruehl, Claus; Wieland, Thomas; Schneider, Stefan W.; Nobiling, Rainer; Wagner, Andreas H.; Hecker, Markus (Thrombosis and Haemostasis, 2015)
Co-stimulation via CD154 binding to CD40, pivotal for both innate and adaptive immunity, may also link haemostasis to vascular remodelling. Here we demonstrate that human platelet-bound or recombinant soluble CD154 (sCD154) elicit the release from and tethering of ultra-large (UL) von Willebrand factor (vWF) multimers to the surface of human cultured endothelial cells (ECs) exposed to shear stress. This CD40-mediated ULVWF multimer release from the Weibel-Palade bodies was triggered by consecutive activation of TRAF6, the tyrosine kinase c-Src and phospholipase Cγ1 followed by inositol-1,4,5 tris-phosphate-mediated calcium mobilisation. Subsequent exposure to human washed platelets caused ULVWF multimer-platelet string formation on the EC surface in a shear stress-dependent manner. Platelets tethered to these ULVWF multimers exhibited P-selectin on their surface and captured labelled monocytes from the superfusate. When exposed to shear stress and sCD154, native ECs from wild-type but not CD40 or vWF-deficient mice revealed a comparable release of ULVWF multimers to which murine washed platelets rapidly adhered, turning P-selectin-positive and subsequently capturing monocytes from the perfusate. This novel CD154-provoked ULVWF multimerplatelet string formation at normal to fast flow may contribute to vascular remodelling processes requiring the perivascular or intravascular accumulation of pro-inflammatory macrophages such as arteriogenesis or atherosclerosis.
Keywords: CD40; CD154; endothelial cells; von Willebrand factor; platelets; monocyte/macrophages; remodelling; vascular